2009
DOI: 10.1088/0004-637x/698/2/2131
|View full text |Cite
|
Sign up to set email alerts
|

HARD X-RAY FLARE SOURCE SIZES MEASURED WITH THERAMATY HIGH ENERGY SOLAR SPECTROSCOPIC IMAGER

Abstract: Ramaty High Energy Solar Spectroscopic Imager (RHESSI) observations of 18 double hard X-ray sources seen at energies above 25 keV are analyzed to determine the spatial extent of the most compact structures evident in each case. The following four image reconstruction algorithms were used: Clean, Pixon, and two routines using visibilities-maximum entropy and forward fit (VFF). All have been adapted for this study to optimize their ability to provide reliable estimates of the sizes of the more compact sources. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 27 publications
5
90
2
Order By: Relevance
“…The CLEAN beam factor found for these flares lay in the range 1.9−2.4, suggesting the optimum value is 2 (Dennis & Pernak 2009;Kontar et al 2010), instead of the default value of 1. Figure 1 shows CLEAN maps for the four flares at lowest (10−11.3 keV) and highest (88.6−100 keV) energy bins.…”
Section: Imaging Spectroscopymentioning
confidence: 92%
See 2 more Smart Citations
“…The CLEAN beam factor found for these flares lay in the range 1.9−2.4, suggesting the optimum value is 2 (Dennis & Pernak 2009;Kontar et al 2010), instead of the default value of 1. Figure 1 shows CLEAN maps for the four flares at lowest (10−11.3 keV) and highest (88.6−100 keV) energy bins.…”
Section: Imaging Spectroscopymentioning
confidence: 92%
“…Since we rely on the source sizes taken from the reconstructed images, we verified the best CLEAN beam width for each flare. Dennis & Pernak (2009) and Kontar et al (2010) have pointed out that CLEAN images usually have systematically larger sizes than other algorithms when using the default beam width factor of 1.0. To ensure the best possible determination of the source sizes using CLEAN images, we applied the visibility forward-fitting procedure (Schmahl et al 2007) on the footpoints of each flare, adjusted the CLEAN beam size, and re-calculated the images until the FWHM of the footpoint from both algorithms had the same size.…”
Section: Imaging Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Kašparová et al 2005). Dennis & Pernak (2009) reported that the average semiminor axis of 18 double source flares is about 4 , while a few of the X-ray source sizes were found to be consistent with line sources along the flare ribbons. While the quantitative comparison with the RHESSI observations requires additional work, we note that zero sizes are either the artifacts of the algorithms used or are caused by the very low source heights.…”
Section: Discussionmentioning
confidence: 99%
“…Hereafter, following RHESSI measurements (Kontar et al 2008b;Dennis & Pernak 2009;Prato et al 2009) we will refer to the source sizes in terms of FWHM (Full Width Half Maximum), FWHM x,y = 2 √ 2 ln 2σ x,y . The scattered X-ray flux depends on the cosine of the heliocentric angle of the source (μ ≡ cos(θ)) or equivalently on the position of the source at the solar disk, μ = 1 − (x 2 + y 2 )/R 2 .…”
Section: Spatial Characteristics Of the Primary Backscattered And Obmentioning
confidence: 99%